THE RELATIONSHIP BETWEEN THE EFFECT OF IMMUNOGLOBULIN THERAPY AND THE FUNCTIONAL POTENCIES OF THE CELLULAR LINK OF THE IMMUNE SYSTEM IN X-LINKED AGAMMAGLOBULINEMIA - L. P. Sizyakina; I. I. Andreeva; D. I. Danilova (Медицинский вестник Юга России, 2020)
Objective: to evaluate the effectiveness of intravenous immunoglobulins in X-linked agammaglobulinemia, to identify changes in the cellular link of the innate and adaptive immune response associated with an insufficient effect of replacement therapy. Materials and methods: 12 patients with X-AGH were under dynamic observation. BTK genetic defect confirmed using next generation sequencing technology. After verification of the diagnosis, patients received IVIG replacement therapy at a saturation dose and then at a maintenance dose. The data of prospective observation for a full year of regular IVIG therapy with an assessment of the severity of the disease, monthly monitoring of the pre-transfusion IgG level and determination of the quantitative and functional parameters of the components of the adaptive and innate immune response every three months are presented. Results: regular replacement therapy contributed to a decrease in the frequency of exacerbations of foci of chronic infection, a decrease in the frequency and duration of antibiotic therapy, however, in 30 % of cases, the frequency of exacerbations remained high, and antibiotic courses were doubled than the standard ones. A comparative analysis of the parameters of the immune system showed that with a smaller effect of IVIG, the functional potentials of T-effectors are less significant than in the comparison group and the properties of neutrophils and natural killers are more inhibited. Summary: the relationship between the severity of the clinical manifestation of XLA on the background of replacement therapy and the preservation of the functional potencies of the cellular components of the immune system provides the basis for a possible combination of IVIG therapy with drugs that affect the properties of cellular elements of the immune system.